On Privacy Preserving Data Mining Techniques: Merits and Demerits - Mohana Chelvan, P; Perumal, K (International Journal of Computer Sciences and Engineering, 2025)
Data mining is the process that extracts previously not known valid and actionable information from large archived data to make crucial business and strategic decisions. In recent years, privacy preserving data mining techniques has been studied and more research has been done in this area due to proliferation of internet in everyday life along with huge availability of personal data. Huge volume of microdata is produced on every minute due to e-governance and e-commerce which contains private data about individuals and businesses. The data has been modified in some way to preserve the privacy of individuals. The main goal of privacy preserving data mining is hiding an individual’s sensitive identity and at the same time maintains the usability of data. This paper will give an overview about these rapidly changing techniques and their advancements.